Revisiting the finance-inequality nexus in a panel of African countries - Christelle Meniago; Simplice Asongu (African Governance and Development Institute (AGDI), 2018)
The study assesses the role of financial development on income inequality in a panel of 48 African countries for the period 1996 to 2014. Financial development is defined in terms of depth (money supply and liquid liabilities), efficiency (from banking and financial system perspectives), activity (at banking and financial system levels) and stability while, three indicators of inequality are used, namely, the: Gini coefficient, Atkinson index and Palma ratio. The empirical evidence is based on Generalised Method of Moments. When financial sector development indicators are used exclusively as strictly exogenous variables in the identification process, it is broadly established that with the exception of financial stability, access to credit (or financial activity) and intermediation efficiency have favourable income redistributive effects. The findings are robust to the: control for unobserved heterogeneity in terms of time effects and inclusion of time invariant variables as strictly exogenous variables in the identification process. The findings are also robust to the Kuznets hypothesis: a humped shaped nexus between increasing GDP per capita and inequality. Policy implications are discussed.
Keywords: D60; E25; G20; I30; O55; 330; Africa; Finance; Inequality; Poverty